Introduction to personality - Burger, Jerry M. (Australia Wadsworth/Cengage Learning, 2011)
This proven text fuses the best of theory-based and research-based instruction to give you a powerful introduction to personality that is accessible and understandable. Burger pairs "theory, applications, and assessment" chapters with chapters that describe the research programs aligned with every major theoretical approach. Biographical sketches of theorists and accounts of the stories behind influential research programs help you gain an understanding of how classic and contemporary findings relate to each other, and reinforce the idea that theory and research perpetuate one another. In-text self-assessments and a Study Guide (available separately) allow you to stop, consider what you're reading, and interact with the material.
International edition.
Includes bibliographical references (pages 456-502) and indexes.
Keywords: Personality